The Role of Distance Education in Detecting Talent Indicators in Kindergarten from the Teachers’ Distance - Kurdi, Sandi Farooq; Al-Harbi, Shatha Nasser; Al-Balawi, Faten Hamoud; AL-Arwi, Majeda Dahi; Al-Juhani, Mayar Saeed; Al-Humedi, Wafa Saleem (Journal of Educational and Psychological Sciences, 2021)
The current study aimed to know the role of Distance education in revealing the talent indicators, whether cognitive or personality, in kindergarten from the teachers’ Distance in the Madinah region, to demonstrate the importance of teachers’ observation on children’s talent indicators during the virtual classroom. In order to achieve this, the questionnaire tool was prepared according to several specifications. For the purpose of getting accurate results, the Alpha Cronbach coefficient was used, and the quantitative descriptive method was used for the study. The sample of the study reached (123) teachers. To begin with, the results of the study indicated that: all statements in both cognitive-behavioral indicators (general educational, linguistic, mathematical thinking) and personal behavioral indicators (social-emotional, creative, motivation) were completely limited to the extent that they are high. Moreover, there were no statistically significant differences between governmental and private kindergartens among children in the talent indicators. However, there were statistically significant differences between the governmental and private kindergartens among children in the talent indicators in favor of the age group (from 5 to 6 years) for the age group (from 4 Years to less than 5 years). Lastly, there were no statistically significant differences between females and males among children in giftedness indicators.